2009
DOI: 10.1175/2008mwr2532.1
|View full text |Cite
|
Sign up to set email alerts
|

Objective Classification of Precipitating Convective Regimes Using a Weather Radar in Darwin, Australia

Abstract: A clustering algorithm was applied to Frequency with Altitude Diagrams (FADs) derived from 4 yr of hourly radar data to objectively define four tropical precipitation regimes that occur during the wet season over Darwin Australia. The precipitation regimes defined are distinguished in terms of convective intensity, presence of stratiform precipitation, and precipitation coverage. Regime 1 consists of patchy convection of medium intensity and low area coverage, and regime 2 contains strong convection with relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We begin by summarizing the areal distribution of storm reflectivity values with height using contoured coverage altitude diagrams (CCAD) to further understand the relative differences between overshooting convection in both regimes. The CCAD is similar to the contoured frequency altitude diagrams used by Yuter and Houze [] except that reflectivity bin counts are divided by the total radar‐observable area at each height level following Caine et al []. First, reflectivity values ranging from 5 to 75 dBZ are tallied in 5 dBZ wide bins (5–10, 10–15 dBZ, etc.).…”
Section: C‐pol Reflectivitymentioning
confidence: 99%
“…We begin by summarizing the areal distribution of storm reflectivity values with height using contoured coverage altitude diagrams (CCAD) to further understand the relative differences between overshooting convection in both regimes. The CCAD is similar to the contoured frequency altitude diagrams used by Yuter and Houze [] except that reflectivity bin counts are divided by the total radar‐observable area at each height level following Caine et al []. First, reflectivity values ranging from 5 to 75 dBZ are tallied in 5 dBZ wide bins (5–10, 10–15 dBZ, etc.).…”
Section: C‐pol Reflectivitymentioning
confidence: 99%
“…The algorithm has been used to investigate the detailed evolution of vertical motion and reflectivity fields in different weather systems Black et al 1996) and precipitation regimes (Caine et al 2009). In this study, CFADs were computed in convective regions that were roughly defined as areas within 10-km radius of the stormcell locations (Steiner et al 1995) identified by the SCIT algorithm (Johnson et al 1998).…”
Section: Composite Vertical Structuresmentioning
confidence: 99%
“…A standard approach is to compare contoured frequency with altitude diagrams (CFADs) derived from both model and observed data (Rogers et al 2007;Van Weverberg et al 2011;Caine 2009;Caine et al 2009). Similar to the creation of CFADs, another approach is to calculate the coverage of an observed quantity and compare these measurements with model data.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have analyzed convective-permitting simulations during TWP-ICE (e.g., Wapler et al 2010;Caine 2009;Varble et al 2011;Fridlind et al 2012;Wapler and Lane 2012), exploring aggregate properties of the convective processes and their sensitivity to physical parameterizations. In the spirit of providing a proof of concept of the TITAN analysis, the simulations presented herein are designed specifically with the comparison to radar in mind, and the simulations do not encompass the entire TWP-ICE period, only a 5-day period during the break regime.…”
Section: Introductionmentioning
confidence: 99%